1 - An Examination of the Financial Intelligence Act of Botswana - Mogomotsi, Goemeone E.J. (Africa Development, 2019)
This article provides an analysis of the Financial Intelligence Act of Botswana in respect of the implementation of international anti-money laundering (AML) standards in Botswana. It examines the extent to which Botswana has incorporated, within its legislative framework, the recommendations of the Eastern and Southern African Anti-Money Laundering Group (ESAAMLG) contained in the first Mutual Evaluation Report. Following concerns raised by the ESAAMLG on the effectiveness of the country’s AML regulatory framework in 2007, Botswana promulgated the Financial Intelligence Act which is intended to address money laundering risks and compliance issues. This article generally discusses the institutional framework established by the Act and the obligations imposed on the specified parties under the Act. It narrowly focuses on the statutory obligations, to identify customers and keep records by specified parties. It examines the extent to which the provisions of the Financial Intelligence Act comply with Financial Actions Task Force (FATF) recommendations pertaining to customer identification and record-keeping. It is observed that the Act did not until recently provide for enhanced due diligence relating to Politically Exposed Persons. It is further observed that the independence of the Director General of the Financial Intelligence Agency may be threatened under certain circumstances. However, it is generally observed that the Act has made considerable efforts in complying with FATF standards. Finally, the article makes necessary policy recommendations.